Promising sponge derived marine fungi as antibacterial and biofilm inhibitors - Dyan Wigati, Erna Prawita Setyowati, Sylvia Utami Tunjung Pratiwi, Ari Satia Nugraha (Journal of Applied Pharmaceutical Science, 2024)
Marine organisms, especially sponges, provide many sources of metabolites with various biological activities. Most sponges associate with microbes such as fungi. To solve the problem of sponge availability, it is necessary to isolate compounds from marine-derived fungi due to their feasibility and advantages. This study, thus, highlights that the most prominent genera to produce metabolites active as antibacterials and antibiofilm were Aspergillus, Penicillium, Neosartorya, and Trichoderma. The summarized data of isolated compounds related to antibacterial and antibiofilm activities until 2022 included anthraquinones, sterigmatocystin analogs, hydroxy pyrrolidine alkaloids, helvolic acid derivatives, lactones, prenylated phenylbutyrolactones, citrinin and derivatives, bisthiodiketopiperazine, cyclotetrapeptides, dihydrochromone dimers, amino lipopeptides, furan derivatives, aspiron-derivatives, halogenated metabolites, and alkaloids. Since the biofilm mechanism is very complex, some antibacterial compounds do not necessarily work as antibiofilms. Nevertheless, it can be concluded that compounds produced from sponge-associated fungi have the potential to be developed as new antibacterial and antibiofilm agents although still require further investigation related to the mechanism of actions of the compounds.
Keywords: Marine derive-fungi, antibacterial, antibiofilm, metabolites active, drug development